Republic of Moldova : Staff Report for the 2020 Article IV Consultation and Sixth Reviews Under the Extended Credit Facility and Extended Fund Facility Arrangements-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents 2019 Article IV Consultation with the Republic of Moldova and its Sixth Reviews Under the Extended Credit Facility and Extended Fund Facility Arrangements. Moldova's economic growth remained solid in the first three quarters of 2019, with output expanding nearly 5 percent, supported by strong domestic demand. The three-year program has been broadly successful in achieving its objectives. Comprehensive reforms have rehabilitated the banking system and strengthened financial sector governance, entrenching macrofinancial stability. Prudent and well-coordinated policies are needed to safeguard the progress achieved. Decisive governance and institutional reforms are necessary for faster, sustainable, and inclusive growth. Safeguarding central bank independence is a priority. The inflation-targeting (IT) regime remains appropriate, but additional efforts are needed to improve policy credibility, promote exchange rate flexibility, and disincentivize foreign currency intermediation. Widespread governance and institutional vulnerabilities are major impediments to accelerating income convergence. Addressing these could have significant growth dividends through faster capital accumulation, reduced labor and human capital headwinds from emigration, and higher productivity.